The Astrological Works of Jean Thenaud : Critical French Edition, English Translation, Introduction, and Notes - Virastau, Nicolae Alexandru, (Brill's Studies in Intellectual History ;, 2025)
This critical edition highlights the astrological writings of Jean Thenaud, a sixteenth-century astrologer at the French court who served Louise of Savoy and her son, King Francis I. Thenaud's works provide a rare glimpse into the intense fascination with astrology at the Renaissance court, particularly during the crisis of 1524, when planetary conjunctions led to widespread fears of floods and natural disasters. By creatively incorporating Lucian of Samosata's dialogues, Thenaud also crafted one of the earliest cosmic journeys in early modern European literature. This book enriches our understanding of how astrology, prophecy, politics, and literature interacted in shaping early modern European thought.